2023
DOI: 10.1186/s12974-023-02731-y
|View full text |Cite
|
Sign up to set email alerts
|

Old age promotes retinal fibrosis in choroidal neovascularization through circulating fibrocytes and profibrotic macrophages

Abstract: Background Retinal fibrosis affects 40–70% of neovascular age-related macular degeneration patients. This study investigated the effect of ageing on subretinal fibrosis secondary to choroidal neovascularization and the mechanism of action. Methods Subretinal fibrosis was induced in young (2.5-month) and aged (15–16-month) C57BL/6J mice using the two-stage laser protocol. Five and 30 days later, eyes were collected and stained for CD45 and collagen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The underlying mechanisms of subretinal fibrosis secondary to nAMD are complicated and remain incompletely elucidated. Extensive literature corroborated the involvement of additional factors, such as pericyte-myofibroblast transition (PMT) [ 53 ], EndMT [ 54 ], activated microglia [ 55 ], macrophages [ 56 ] and Müller glia [ 57 ] in the laser-induced CNV mouse model, which contribute to the accumulation of differentiated myofibroblasts and deposition of ECM, ultimately leading to fibrosis formation in nAMD. Therefore, the contribution of Wnt5a or Wnt/β-catenin in the MT of other cell types during subretinal fibrosis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of subretinal fibrosis secondary to nAMD are complicated and remain incompletely elucidated. Extensive literature corroborated the involvement of additional factors, such as pericyte-myofibroblast transition (PMT) [ 53 ], EndMT [ 54 ], activated microglia [ 55 ], macrophages [ 56 ] and Müller glia [ 57 ] in the laser-induced CNV mouse model, which contribute to the accumulation of differentiated myofibroblasts and deposition of ECM, ultimately leading to fibrosis formation in nAMD. Therefore, the contribution of Wnt5a or Wnt/β-catenin in the MT of other cell types during subretinal fibrosis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that the miR-128 expression was significantly lower in patients with Ikzf1 deletion than those without Ikzf1 deletion in B-cell precursor acute lymphoblastic leukemia ( Krzanowski et al, 2017 ). Importantly, these hub genes not only participate in immune regulation but also play important roles in neurodegenerative diseases through the ceRNA network regulation ( Javed et al, 2023 ; Yi et al, 2023 ). Qin et al (2023) revealed that miR-6734-3p and its target mRNA Cyth4 expression were correlated with patients’ age in Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Aging, a major risk factor for fibrotic processes, contributes to organ fibrosis incidence, particularly evident in proliferative diabetic retinopathy and neovascular age-related macular degeneration (nAMD). Fibrosis-related conditions including nAMD and choroidal neovascularization (CNV), secondary to other eye diseases, with aging promoting CNV-induced subretinal fibrosis [55]. Human choroidal vasculature undergoes aging changes, evidenced by age-related decreases in overall choroidal thickness, choriocapillaris density, vessel diameter, and choroidal blood flow.…”
Section: Choroidal Vascular Aging: Pathophysiological Insightsmentioning
confidence: 99%